Causes of Death After Neuroendocrine Tumors Diagnosis: A US Population-Based Analysis. Issue 1 (January 2021) - Sonbol, Mohamad Bassam; Saad, Anas M.; Gonzalez-Velez, Miguel; Starr, Jason; Halfdanarson, Thorvardur R.
Abstract : Objective: In this study, we aimed to determine the cause of death (COD) after the diagnosis of neuroendocrine tumors (NET). Methods: We used the Surveillance, Epidemiology and End Results (SEER) Program to review patients diagnosed with NET during 2000 to 2016. Patients were followed until death, and different CODs were determined. Results: Of 94, 399 patients with NETs, 40.9% died during the study period. During the first year of diagnosis, most deaths were from NETs (73%), followed by other cancers (11.2%) and cardiac diseases (4.6%). After more than 10 years, NET deaths decreased to 24.3%, whereas other cancers and cardiac disease became more common. Neuroendocrine tumors were responsible for 42.8%, 63.4%, and 81.2% of deaths in grade I, grade II, and grade III, respectively. For grade I localized NET, other cancers (22.2%) were the most common COD followed by NET (19.7%), whereas in grade 2 localized NET, NET was COD in 31.1% of cases followed by other cancers (22.4%). In metastatic disease, NET was the most common COD regardless of grade. Conclusions: For low-grade localized NET, deaths were mostly secondary to non-NET causes. In contrast, NET is responsible for most of deaths in metastatic NET regardless of grade. Abstract : Supplemental digital content is available in the text.